2013
DOI: 10.3945/ajcn.112.047829
|View full text |Cite
|
Sign up to set email alerts
|

11β Hydroxysteroid dehydrogenase type 2 and dietary acid load are independently associated with blood pressure in healthy children and adolescents

Abstract: A lower 11βHSD2 activity and higher dietary acid load may independently contribute to higher systolic BP in healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…1, 522 records were accessed by searching the scientific databases of which 316 records remained after removing the 206 duplicate references. After exclusion of irrelevant studies, sixteen cohort studies (6,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and seventeen cross-sectional studies (1,11,12,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) were included in the current systematic review. Characteristics of the included studies, which were published between 2005 and 2017, are shown in Table 1.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…1, 522 records were accessed by searching the scientific databases of which 316 records remained after removing the 206 duplicate references. After exclusion of irrelevant studies, sixteen cohort studies (6,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and seventeen cross-sectional studies (1,11,12,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) were included in the current systematic review. Characteristics of the included studies, which were published between 2005 and 2017, are shown in Table 1.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The sample size of these studies ranged from sixty-three to 92 478 individuals, and totally just 3574 individuals were aged 17 years or younger. Of thirty-three included studies, eleven were conducted in the Asia (1,11,12,22,25,27,30,37,38,41) , fourteen in Europe (6,13,17,20,21,23,24,26,29,31,32,34,36,43) and eight in the USA (18,19,28,33,35,39,42,44) . Four studies were done on men (13,17,33,43) , five on women (12,18,21,23,32) and the remaining studies implied on both genders.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This enzyme oxidizes cortisol (F) into inactive cortisone (E), thereby rendering the mineralocorticoid receptor-hormone complex inactive (1). The enzymatic activity of 11β-HSD2 can be estimated using the ratios of these hormones in urine (2)(3)(4)(5) and saliva (Sal) fluids (4,6,7). Subtle deficiencies in 11β-HSD2 activity have been reported in subsets of hypertensives and normotensives (8,9), whereas more severe hypertension and hypokalemia are observed in cases of substantial or complete loss of 11β-HSD2 activity (1,9).…”
Section: Introductionmentioning
confidence: 99%